The properties of the oils obtained from liquefaction of poplar wood summary - Yilgin, M.; Pehlivan, D. (Scientific and Technical Research Council of Turkey, 2000)
The effects of various catalysts (Na2CO3, K2CO3 and HCOOH) on the liquefaction of 10 % aqueous slurry of poplar wood under high temperature and pressure conditions was investigated. The results of liquefaction reaction were evaluated in terms of oil yield, water-soluble solids, solid residue and gas products. The oil yields were 35.2% in the experiment with HCOOH as catalyst, 23.4, 28.8 and 25.5 % with Na2CO3 gravimetric (TG) analyses of the oils were also undertaken. The FTIR spectra of the oils were similar, contained bands assigned to lignitic structures and confirmed their abundance. It was also found that alkali catalysts exhibited their known effects on the lignitic chemical structures in the wood.; The effects of various catalysts (Na2CO3, K2CO3 and HCOOH) on the liquefaction of 10% aqueous slurry of poplar wood under high temperature and pressure conditions was investigated. The results of liquefaction reaction were evaluated in terms of oil yield, water-soluble solids, solid residue and gas products. The oil yields were 35.2% in the experiment with HCOOH as catalyst, 23.4, 28.8 and 25.5% with Na2CO3 and K2CO3 catalyts and non-catalytic runs respectively. Fourier Transform Infrared (FTIR) and Thermal gravimetric (TG) analyses of the oils were also undertaken. The FTIR spectra of the oils were similar, contained bands assigned to lignitic structures and confirmed their abudance. It was also found that alkali catalysts exhibited their known effects on the lignitic chemical structures in the wood.
Kavak odununun sivilastirilmasindan elde edilen yaglarin ozellikleri
Keywords: FTIR; Liquefaction; Poplar wood; Pyrolitic oil; TGA